Antioxidant and antidiabetic activities of a polyphenol rich extract obtained from Abelmoschus esculentus (okra) seeds using optimized conditions in microwave-assisted extraction (MAE) - Woumbo, Cerile Ypolyte; Kuate, Dieudonné; Metue Tamo, Danielle Gaelle; Womeni, Hilaire Macaire (Frontiers in Nutrition, 2022)
Functional foods have gained popularity in recent decades. They are exploited for their bioactive compounds like polyphenols, which are highly demanded in cosmetic, pharmaceutical and nutraceutical industries. However, extractive techniques and conditions used up to recently are almost obsolete and must be optimized for higher efficiency. The current study aimed to evaluate the antidiabetic potential of an optimized extract of Abelmoschus esculentus (okra) seeds. The optimal conditions for extracting polyphenolic compounds from okra seeds were determined using Microwave Assisted Extraction (MAE). A Face Center Composite Design (FCCD) was used for optimization. Solvent/dry matter ratio, wavelength and time were considered while the response studied was the polyphenolic content. The extract obtained at optimal conditions was characterized using Thin Layer Chromatography (TLC) and Fourier Transform Infra-Red (FTIR) spectroscopy, then tested for its antioxidant, alpha amylase inhibitory and antidiabetic activities. Response Surface Methodology (RSM) permitted the determination of the optimal conditions for phenols extraction as: microwave power 330 W, with a solvent ratio of 97.04/1 mL/g for 9.5 min of extraction time. The optimized extract showed a phenolic content up to 86.37 ± 1.13 mg GAE/g containing quercetin and catechin as revealed by the TLC. Functional groups characteristic of polyphenols were identified on FTIR spectra, and the extract exhibited good in vitro antioxidant capacities with DPPH (2, 2-diphenyl-1-picrylhydrazyl) radical scavenging capacity and FRAP (Ferric Reducing Antioxidant Power Assay). An IC50 of 3.99 ± 0.15 μg/mL was obtained with the DPPH scavenging test. Alpha amylase inhibitory assay revealed that the optimized okra extract behaved as a non-competitive inhibitor of porcine pancreatic amylase with an IC50 of 484.17 ± 2.33 μg/mL. Antidiabetic activity of the extract was observed in streptozotocin-induced diabetic males Wistar rats, as shown by the fasting blood glucose levels, food intake, changes in body weight and serum lipid profile among others.